Administration Rates of the Tdap Vaccine in Obstetric Patients. Issue 7 (July 2018) - Koerner, Jamie; Forinash, Alicia B.; Yancey, Abigail M.; Brinkmeyer, Jessica; Dingman, Spencer; Miller, Collin; Thompson, Judy; Bergin, Laura; López, Julia D.; Ravin, Amy
Background: Infants younger than 6 months of age are at high risk for contracting pertussis because of not being fully vaccinated. The Advisory Committee on Immunization Practices (ACIP) recommends vaccinating all pregnant women with tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis vaccine (Tdap) between 27 and 36 weeks to offer passive immunity to the infant to help protect them until they are able to receive the full pertussis series.Objective: To assess and compare compliance with the 2013 ACIP recommendation of vaccinating pregnant women with Tdap at 27 to 36 weeks' gestation in 2 obstetric clinics.Methods: This cross-sectional, retrospective chart review evaluated Tdap vaccine compliance in a random sample of obstetric patients from October 2013 to September 2014. The primary outcome evaluated the proportion of patients who received Tdap between 27 and 36 weeks' gestation. Secondary outcomes included the proportion of patients who received Tdap at any point in pregnancy and within 30 days postpartum.Results: The charts of 573 patients were reviewed, and 237 met inclusion criteria. For the primary outcome, 142 patients (59.9%) received the Tdap vaccine. Overall, 156 patients (65.8%) received Tdap at some point during the pregnancy. Factors associated with receiving the Tdap vaccination were insurance status, prenatal care risk level and site of prenatal care, receipt of the influenza vaccine, and preterm labor in the current pregnancy.Conclusion: The Tdap vaccine rate was 65.8%, with 59.9% of patients receiving the vaccine within the recommended ACIP timeframe. Further education, improvements in documentation, and chart reminders are needed to enhance administration.